2015
DOI: 10.1111/aas.12542
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acute stroke cerebral CT examinations by anaesthesiologists

Abstract: Background and purposeIt is essential to diagnose ischaemic stroke as soon as possible after symptom onset, so that thrombolytic treatment can be initiated as quickly as possible. This might be greatly facilitated if cerebral CT could be carried out in a pre‐hospital setting. The aim of this study was to evaluate if anaesthesiologists, who in Norway provide pre‐hospital medical care, could be trained to assess cerebral CT scans to exclude radiological contraindications for thrombolytic stroke treatment.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…Because the administration of prehospital thrombolysis is increasingly being studied at many stroke centers in several countries [3,6,7,8,9,10,11,12,13,14], the availability of a tool that could evaluate CT images and detect signs of infarction in an ambulance in a standardized manner would be of considerable medical interest. This study demonstrates the feasibility and potential clinical benefit of integrating the e-ASPECTS software for the automated detection of early ischemic damage in a MSU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the administration of prehospital thrombolysis is increasingly being studied at many stroke centers in several countries [3,6,7,8,9,10,11,12,13,14], the availability of a tool that could evaluate CT images and detect signs of infarction in an ambulance in a standardized manner would be of considerable medical interest. This study demonstrates the feasibility and potential clinical benefit of integrating the e-ASPECTS software for the automated detection of early ischemic damage in a MSU.…”
Section: Discussionmentioning
confidence: 99%
“…This work was part of the prehospital stroke treatment program in which the MSU was dispatched mainly to hyperacute stroke patients. Moreover, the response times of the MSU and the times to diagnostic work-up are faster than those in the conventional hospital approach [6,7,8,9,10,11,12,13,14]. Indeed, the finding of very high e-ASPECTS values matched with the findings of median scores of 9 in a recent thrombectomy study, in which response times were also very short (median symptom onset-to-needle times of 85 min) [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Det trengs ingen radiograf for å gjennomføre en CT-undersøkelse, slik at utgiftene vil begrense seg til innkjøp og vedlikehold av CT-maskin. Norsk forskning i regi av Stiftelsen Norsk Luftambulanse har vist at anestesileger lett kan laere å ta og tolke CT-bilder av akutte hjerneslagpasienter (Hov et al, 2015). CTbasene vil etablere direkte teleradiologi med regionsykehuset i helseforetaket.…”
Section: Status Og Utfordringerunclassified
“…Currently, several programs for prehospital stroke diagnosis and treatment are in operation (in Berlin since 2011, in Frederikshavn, Norway, since 2013, in Houston, Texas, since 2014, and in Cleveland, Ohio, since 2014), and several other ambulances have been implemented or are being planned. Additional studies have confirmed that such programs have resulted in an enormous time gain and that treatment rates have increased significantly …”
Section: Introductionmentioning
confidence: 99%